(untitled) (La U Investiga, 2018)
Arterial hypertension (hypertension) and atherosclerosis are closely linked and in this relationship the renin-angiotensin system (ARS) plays a leading role, since it participates in the progression of vascular disease. The objective of this study was to present a review of the molecular and cellular pathophysiological mechanisms of the effect of lipoproteins on the genesis of HT. The search strategy included review and observational studies, systematic review and meta-analysis of the biomedical literature about biochemical and physiological aspects associated with hypertension, with the following search terms: obesity and overweight, high blood pressure, dyslipidemia, endothelial dysfunction, resistance to insulin and diabetes mellitus. To this end, a search was conducted between March and October 2018 in the LILACS, MEDLINE-PubMed and Cochrane Library databases. Results and conclusions the detection of endothelial dysfunction in people with arterial hypertension has prognostic and therapeutic importance, since it allows the intensity of the treatment needed to avoid complications. The correction of endothelial dysfunction can be considered an objective of treatment to try to stop the atherosclerotic process and improve the prognosis. The behavior must be integral to include the different pathophysiological, hemodynamic and metabolic aspects involved in the health-disease process of each individual.